Porous metal oxide-carbon composite with hollow structure for energy storage applications - Adhikari, Surya Prasad (Journal of Innovations in Engineering Education, 2019)
Nanocomposite structure of porous hollow TiO2 nanofibers (NFs) and graphitic carbon nitride (g-C3N4) sheets were directly fabricated by means of a novel electrospinning combined with calcination process. Owing to the high porosity, these nanostructured demonstrate enhanced energy storage properties when used in supercapacitors (SCs). Nanomaterials in particular offer unique properties or combinations of properties as electrodes and electrolytes in a range of energy devices. The energy storage behavior of electrochemical capacitors (ECs) made from TiO2/g-C3N4 nanocomposites was investigated by cyclic voltammetry and electrochemical impedance spectra. These tests showed that the supercapacitive performance of g-C3N4 was significantly enhanced after attaching porous TiO2 nanofibers.